Characterizing the parent and alkyl polycyclic aromatic hydrocarbons in the Pearl River Estuary, Daya Bay and northern South China Sea: Influence of riverine input. (April 2015) - Yuan, Ke; Wang, Xiaowei; Lin, Li; Zou, Shichun; Li, Yan; Yang, Qingshu; Luan, Tiangang
Abstract: Distributions of 31 parent polycyclic aromatic hydrocarbons (PAHs) and 29 alkyl PAHs in surface sediments of the Pearl River Estuary (PRE), Daya Bay (DYB) and northern South China Sea (SCS) were examined to study the influence of riverine input. It was found that the contributions of riverine input to sediment PAHs in PRE was much higher than other areas. However, higher proportion of alkyl PAHs and low molecular weight PAHs in DYB and the northern SCS was observed, indicating their different sources. Nevertheless, the sediment PAHs in PRE were heterogeneous and affected by the hydrodynamic conditions. The high molecular weight PAHs were dominant in PRE and enriched in the depositional area of suspended particular matter (SPM). Moreover, the concentration of PAHs in SPM was similar to those in surface sediments and dominated in water columns. Therefore, SPM played a very important role in transportation and distribution of PAHs in PRE. Graphical abstract: Highlights: EPA 16 PAHs contributed a small amount of total PAHs. Alkyl PAHs showed different behaviors from parent PAHs. High weight PAHs preferably indicated riverine input. PAHs distribution in sediment was related with the suspended particle deposition. Abstract : Suspended particular matter played a very important role in distribution of PAHs in tide-dominated estuary and alkyl PAHs showed different behavior from parent PAHs.